2014
DOI: 10.1007/s40615-014-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Related Chronic Health Conditions as Predictors of Motivation to Engage in Healthy Eating Behaviors Among Black Adults

Abstract: Introduction Blacks in the USA have a high prevalence of obesity and therefore suffer disproportionately from obesityrelated chronic health conditions. Eating a poor diet is a major contributor to obesity and obesity-related chronic health conditions (e.g., heart disease, hypertension, type 2 diabetes) in Blacks. Having medical concerns has been identified in earlier research to be a motivator to eat a healthy diet among Blacks. Purpose The purpose of this study was to examine body mass index (BMI) as a predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…For the mediator situational motivation, which is defined as motivation experienced during a particular activity [ 32 ], the shopping task, swap offer, Nutri-Score label, and norm message are expected to increase situational motivation because presence of the interventions increases involvement with the product [ 33 ]. Being presented with a healthier alternative makes consumers aware of the (un)healthfulness of their food choice which subsequently may motivate them to behave more healthily (hypothesis 3) [ 34 ]. Additionally, presence of and attention to the Nutri-Score label make healthfulness information more salient, which may remind consumers about healthy eating and thus motivate them to make a healthy choice in this particular shopping situation (hypothesis 5) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the mediator situational motivation, which is defined as motivation experienced during a particular activity [ 32 ], the shopping task, swap offer, Nutri-Score label, and norm message are expected to increase situational motivation because presence of the interventions increases involvement with the product [ 33 ]. Being presented with a healthier alternative makes consumers aware of the (un)healthfulness of their food choice which subsequently may motivate them to behave more healthily (hypothesis 3) [ 34 ]. Additionally, presence of and attention to the Nutri-Score label make healthfulness information more salient, which may remind consumers about healthy eating and thus motivate them to make a healthy choice in this particular shopping situation (hypothesis 5) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being presented with a healthier alternative makes consumers aware of the (un)healthfulness of their food choice which subsequently may motivate them to behave more healthily (hypothesis 3) [ 34 ]. Additionally, presence of and attention to the Nutri-Score label make healthfulness information more salient, which may remind consumers about healthy eating and thus motivate them to make a healthy choice in this particular shopping situation (hypothesis 5) [ 34 ]. Descriptive social norms have the ability to influence behavior because people want to follow others’ behavior to behave efficiently [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to studying the link between general self-efficacy and body weight in a representative sample of workers, we leverage research on body size perceptions to examine the role of race and gender as moderators of this relationship. This is an important step forward since research has suggested that both race and gender are tied to body weight (e.g., Baltrus et al, 2005), as well as individual's self-recognition of (e.g., Riggs et al, 2017;Sivalingam et al, 2011) and attitudes regarding (S. M. Harris, 1994;Tucker et al, 2014) body weight issues. Indeed, scholars of body weight have called for more research that includes gender and race in addition to body weight (e.g., Puhl & Brownell, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Demographic characteristics of the respondents were assessed using the Demographic and Health Information Data Questionnaire ( 45 , 46 ). Demographic characteristics reported in this study include respondents' age, height, weight, gender, ethnic origin, whether English was their first language, nativity, acculturation, highest level of education, employment status, U.S. region of residence, relationship status, health insurance status, and annual household income.…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variable, presence of a chronic health condition, was assessed by one question from the Demographic and Health Information Data Questionnaire ( 45 , 46 ). Respondents were asked to indicate all of the health conditions they currently have from the following: high cholesterol, overweight/obesity, heart disease, cancer (specify the type), high blood pressure, type 2 diabetes, other (specify), or to select “I do not have any of these health conditions.”…”
Section: Methodsmentioning
confidence: 99%